Compositional And Frequency Dependent-magnetic And Microwave Characteristics Of Indium Substituted Yttrium Iron Garnet. - Rodziah Nazlan; Mansor Hashim; Ismayadi Ismail; Raba'ah Syahidah Azis; Jumiah Hassan; Zulkifly Abbas; Fadzidah Mohd Idris; Idza Riati Ibrahim (Springer US, 2024)
Indexed by Scopus